Economic evaluation of pig rearing fed with different level of jaggery filter cake along with concentrate - PRASANNA S.B and RAVINDRA KUMAR, b.H.M. PATEL, SANJAY KUMAR (Indian Journal of Animal Production and Management, 2019)
The present study was carried out for economic evaluation of pig rearing fed with different levels of Jaggeryfilter cake along with concentrate. An experiment was designed using 30 Large White Yorkshire piglets (3 Â½month old), randomly divided and maintained on 5 dietary treatment groups, viz. group I: concentrate only,group II: concentrate +250 g JFC, group III: concentrate +500 g JFC, group IV: concentrate +750 g JFC andgroup V: ad lib. JFC only. Jaggery filter cake supplementation was increased in the ratio of 50:100:150 gin group II, III, IV respectively, every fortnight during growing stage and every week during finishing stage.The cost of balanced ration was estimated by considering the prevailing prices of the feed ingredients,mineral salt, common salt and vitablend. The relative cost effectiveness of each diet was thus assessed.Further, the amount incurred for treatment of any disease outbreak was also included in the expenditureunder different groups. By considering the total live weight gain under each treatment, the cost involvedto produce 1 kg live weight gain was calculated. Net profit for each treatment was calculated separatelyby considering the sale price of pork produced at the end of experiment. The total cost during the wholeexperiment was highest in group I (no JFC), followed by group II, group IV and group III and lowest ingroup V (ad. lib JFC with no concentrate). Cost involved for production of 1 kg live weight for group I toV was Rs 35.25, 32.34, 29.48, 29.42 and 19.31, respectively. High cost incurred in group I was due tosole concentrate feeding and lowest cost in group V was due to sole feeding of JFC, respectively. Costinvolved in group IV was marginally higher as compared to group III due to relatively more concentrateintake along with known quantity of JFC.